1998
DOI: 10.1046/j.1365-2362.1998.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertension plasma and human umbilical vein endothelial cells: an in vitro study

Abstract: The present work gives further support to the hypothesis that a circulating factor in gestational hypertension, possibly produced by the fetoplacental unit, causes dysfunction of the vascular endothelial cells and NO reduction, resulting in a loss of vascular refractoriness to vasoactive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…At 80% confluence, cultured HAECs were incubated for 3 h at 37°C with EGM-2 alone (= HAEC), or with 20% (v/v) plasma in EGM-2 (plasma from healthy subjects = HAEC + control plasma, from MCI patients = HAEC + MCI plasma, from AD patients = HAEC + AD plasma) (20). We chose this incubation time since in vitro studies have previously shown that short-term application of Ap eptides to isolated vessels may affect vascular tone (21).…”
Section: Human Aortic Endothelial Cell Culturementioning
confidence: 99%
“…At 80% confluence, cultured HAECs were incubated for 3 h at 37°C with EGM-2 alone (= HAEC), or with 20% (v/v) plasma in EGM-2 (plasma from healthy subjects = HAEC + control plasma, from MCI patients = HAEC + MCI plasma, from AD patients = HAEC + AD plasma) (20). We chose this incubation time since in vitro studies have previously shown that short-term application of Ap eptides to isolated vessels may affect vascular tone (21).…”
Section: Human Aortic Endothelial Cell Culturementioning
confidence: 99%